Exploring adolescents’ food environments in Vietnam: Insights from participatory research - Even, Brice; Nabuuma, Deborah; Truong Tuyet, Mai; Phuong, Ngo Thi Ha; Termote, Celine (2025)
This policy brief synthesizes findings from participatory video research with adolescents in urban, peri-urban, and rural Vietnam. Adolescents documented their daily interactions with local food environments, and these videos formed a shared evidence base for subsequent co-design workshops with adults. The analysis shows that proximity, convenience, affordability, and pervasive marketing are key determinants of adolescents’ food choices. Although home-cooked meals and fresh foods remain valued, near-school retail outlets and digital cues strongly shape day-to-day eating practices and facilitate the increasing penetration of ultra-processed foods and sugar-sweetened beverages. The brief gives an overview of the co-designed community action plans and outlines priority policy options to improve school and retail food environments, including strengthened canteen standards, restrictions on the marketing and sale of sugar-sweetened beverages, improved food and nutrition messaging, and enhanced monitoring and accountability. Overall, the findings highlight the importance of youth-engaged approaches for developing context-specific and equitable strategies to support healthier diets.